Rainfall erosivity and soil erodibility in the northeastern Brazil - Campos Filho, Olívio Ribeiro; Silva, Ivandro de França da; Andrade, Alberício Pereira de; Leprun, Jean Claude (Pesquisa Agropecuaria Brasileira, 1992)
The rainfall erosivity was determined by the method of Wischmeier & Smith (1958) in order to evaluate some factors of the Universal Soil Loss Equation on an Alfisol in Pernambuco (Northeastern Brazil), using different erosion indexes; and the soil erodibility was determined through direct methods with natural rainfall and nomograph. During the study it was evidenced that the EI30 was the best erosion index for rainfall erosivity evaluation, where R factor was 3551 MJ.mm.ha-1.h-1 for a period of ten year studies. Also, it was verified that under the conditions of Glória de Goitá the values of the K factor (0.013 t.ha.h.ha-1.MJ-1.mm-1) determined by the nomographic method was practically equivalent to those determined by the direct method with natural rainfall of 0.014 t.ha.h.ha-1.MJ-1.mm-1 value.